The effects of chronic social stress on cognitive flexibility in adult female macaques - Alvarado, M C; Jonesteller, T; Bailey, K; Gray, A C; Sanchez, M M; Bachevalier, J (bioRxiv, 2025)
Chronic social subordination stress in macaques, particularly when it begins early in life, is associated with negative health and cognitive aging outcomes. Utilizing a longitudinal, translational monkey model of early life stress, we report the cognitive performance of adult female Rhesus macaques ( that had received social subordination stress associated with Low Social Status (LSS) since birth. Social subordination stress is the means by which macaque social groups establish their hierarchical organization. Higher ranked monkeys maintain their rank by aggression towards lower ranked animals, that in order to avoid harassment, engage in submissive behaviors. This chronic social stress in lower ranked monkeys produces physiological stress responses that over time can accelerate biological and cognitive aging. For this study, we compared 25 adult female Rhesus monkeys, 14 of which were of Low Birth Rank and had received higher levels of social subordination stress since infancy resulting in higher chronic stress. The remaining 11 were of High Birth Rank, and had committed, rather than received, social aggression/harassment on lower ranked subjects. These two groups have been followed longitudinally from birth to adolescence to assess long-term behavioral, physiological, and neural consequences of social stress. Now as they reached adulthood (ages 7-8 years), we assessed their cognitive abilities, focusing on executive function/cognitive flexibility, as a first assessment to map the trajectory of cognitive decline with aging. We trained subjects on the Intra-/Extra-dimensional shift task (ID/ED), which is a Wisconsin Card Sort analog using visual stimuli. This task is relevant for age-related cognitive decline, particularly in executive function, and cognitive flexibility. Cognitive results indicated only mild differences between High and Low ranking subjects on the simple discrimination, and the reversal learning stages of the task. We did find an interaction between High Birth Rank and performance across the three dimensional-shift stages, but no main effect of Rank. Thus, at this first age, we detected no performance differences indicating accelerated cognitive decline. We discuss other factors impacting performance, such as social housing and temperament measures and comparisons with neuroimaging data on these subjects.